Environmental chemistry : microscale laboratory experiments - Ibanes, Jorge G. ed; Hernandez-Esparza, Margarita ed; Doria-Serrano, Carmen ed; Fregoso-Infante, Arturo ed; Singh, Mono Mohan ed (Environmental chemistry, 2008)
Summary: This book presents chemical analyses of the most pressing waste, pollution, and resource problems for the undergraduate or graduate student. Its distinctive holistic approach provides a solid introduction to theory as well as a practical laboratory manual detailing beginning and advanced experimental applications. It presents laboratory procedures at microscale conditions, for minimum waste and maximum economy.